Strategi Pengembangan Daya Tarik Wisata Air Terjun di Desa Sambangan - Manalu, Sara Hotnida; Citra, IPutu Ananda; Christiawan, Putu Indra (Sekolah Tinggi Pariwisata AMPTA, 2020)
The research objective was to describe the potential for waterfall tourism in Sambangan Village and to analyze strategies to develop the tourist attraction of the waterfall in Sambangan Village. Collecting data by means of observation, interviews, and document recording was analyzed with qualitative analysis to describe the potential for waterfall tourism in Sambangan Village and SWOT analysis to formulate a waterfall tourism development strategy. The results showed (1) classification of waterfall tourism potential in Sambangan Village, namely the classification of low tourism potential (Barak Wall Waterfall), medium tourism potential classification (Changing Waterfall, Dedari Waterfall, Cemara Waterfall), and high tourism potential classification ( Aling Aling Waterfall, Kembar Waterfall, Kroya Waterfall, Pucuk Waterfall) and (2) A strategic plan for developing a waterfall tourist attraction, namely by developing and improving various components including tourist attractions, accessibility, facilities, institutions, and preservation. environment to increase tourists to the waterfall in Sambangan Village.